Accumulation of Deleterious Mutations in Landlocked Threespine Stickleback Populations. (7th April 2020) - Yoshida, Kohta; Ravinet, Mark; Makino, Takashi; Toyoda, Atsushi; Kokita, Tomoyuki; Mori, Seiichi; Kitano, Jun
Abstract: Colonization of new habitats often reduces population sizes and may result in the accumulation of deleterious mutations by genetic drift. Compared with the genomic basis for adaptation to new environments, genome-wide analysis of deleterious mutations in isolated populations remains limited. In the present study, we investigated the accumulation of deleterious mutations in five endangered freshwater populations of threespine stickleback ( Gasterosteus aculeatus ) in the central part of the mainland of Japan. Using whole-genome resequencing data, we first conducted phylogenomic analysis and confirmed at least two independent freshwater colonization events in the central mainland from ancestral marine ecotypes. Next, analyses of single nucleotide polymorphisms showed a substantial reduction of heterozygosity in freshwater populations compared with marine populations. Reduction in heterozygosity was more apparent at the center of each chromosome than the peripheries and on X chromosomes compared with autosomes. Third, bioinformatic analysis of deleterious mutations showed increased accumulation of putatively deleterious mutations in the landlocked freshwater populations compared with marine populations. For the majority of populations examined, the frequencies of putatively deleterious mutations were higher on X chromosomes than on autosomes. The interpopulation comparison indicated that the majority of putatively deleterious mutations may have accumulated independently. Thus, whole-genome resequencing of endangered populations can help to estimate the accumulation of deleterious mutations and inform us of which populations are the most severely endangered. Furthermore, analysis of variation among chromosomes can give insights into whether any particular chromosomes are likely to accumulate deleterious mutations.